1927 Minn. Gen. Laws 407-08 - (:unkn) unknown (My University, 1927)
An Act Relating to the Minimum Punishment or Penalty for Felonies Committed while Armed with a Firearm, ch. 294, § 1: That if any person shall commit a felony, or attempt to commit a felony, while armed with a pistol, revolver, gun or other firearm, with intent to use the same in the commission thereof, the penalty therefor, including any additional penalty which may be now or hereafter imposed by any law of this State for the commission of a crime of violence while armed with or having available any firearm, shall in the discretion of the trial judge be imprisonment for not less than five years;
Keywords: COMMITTING CRIME W/ WEAPON